Dynamics of Mabims Criteria in Preliminary Determination of Kamariyah: Maqasid Syariah Analysis of Accuracy and Istbat Session Decisions - Frangky Suleman; Misbah Khusurur; Bashori Alwi; Muhajir (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
MABIMS is a method and concept in determining the initial Kamariyah and producing a decision, the Isbat session held by the Ministry of Religion plays an important role in this process where this paper will analyze the determination with a focus on the accuracy and decisions taken from the Isbat session, through the Maqasid as-Shariah approach. This research explores how the MABIMS criteria can fulfill Sharia objectives in maintaining the benefit of the people. This analysis includes an evaluation of the hisab and rukyat used, as well as their implications for the unity of Muslims in the Southeast Asia Region. The results of this research show that even though there are differences in views, the maqasid as-syariah approach can be a basis for reaching more accurate and widely accepted decisions. The method used in analyzing legally a determination made by the state, this approach is used that the initial determination of kamariyah in Indonesia is a complex process involving various aspects of law and regulation. So from the study it can be concluded that the policy of the state leader is something that has been thought about for the benefit of many people with the principle of fiqh rules, namely: tassharuf al-imam ala arra'iyyah manuthu bil mashlahah.